Multicriteria Optimisation in Logistics Forwarder Activities - Poletan Jugović, Tanja; Jugović, Alen; Zelenika, Ratko (Promet - Traffic&Transportation, 2007)
Logistics forwarder, as organizer and planner of coordinationand integration of all the transport and logistics chains elements,uses adequate ways and methods in the process of planningand decision-making. One of these methods, analysed inthis paper, which could be used in optimisation of transportand logistics processes and activities of logistics forwarder, isthe multicriteria optimisation method. Using that method, inthis paper is suggested model of multicriteria optimisation of logisticsforwarder activities. The suggested model of optimisationis justified in keeping with method principles of multicriteriaoptimization, which is included in operation researchmethods and it represents the process of multicriteria optimizationof variants. Among many different processes of multicriteriaoptimization, PROMETHEE (Preference Ranking OrganizationMethod for Enrichment Evaluations) and Promcalc& Gaia V. 3.2., computer program of multicriteria programming,which is based on the mentioned process, were used.